Penguatan Peran Direktorat Jenderal Bina Pembangunan Daerah Kementerian Dalam Negeri (Studi Penyelenggaraan Peraturan Presiden Nomor 1 Tahun 2022 Tentang Rencana Umum Nasional Keselamatan Lalu Lintas Dan Angkutan Jalan Di Daerah) - Simanjuntak, Nancy Fransisca M.; Labolo , Muhadam; Rusfianda , Yudi (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
The evaluation of the National Road Safety Plan (RUNK) for the period 2011-2035 highlighted weaknesses in institutional functions and roles, prompting the Government to issue Presidential Regulation (Perpres) 1 of 2022 regarding the National Road Safety Plan for the period 2021-2040. The Ministry of Home Affairs, through the Directorate General of Regional Development, plays a key role in traffic and transportation management. This research focuses on strengthening the role of the Directorate General of Regional Development in implementing Perpres at the regional level, emphasizing coordination between the central and regional governments, civil society organizations, the transportation industry, and transportation communities to enhance traffic safety. A qualitative descriptive research method was used to gain a deep understanding of the context, processes, and meanings behind the Directorate General's role in policy implementation. In-depth interviews will be conducted to collect data from various stakeholders, while participatory observation will be carried out to directly observe policy implementation. The results of the research indicate that the Directorate General of Regional Development at the Ministry of Home Affairs plays a vital role in improving traffic safety in Indonesia. They have successfully strengthened coordination between the central and regional governments, civil society organizations, the transportation industry, and transportation communities. Through initiatives such as the Road Traffic and Transportation Safety Action Plan (RAK LLAJ) and traffic safety management information systems, the Directorate General has helped identify and address policy gaps and enhance human resource quality in regions.